Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) di Sekolah Dasar - Aulia Pramita Sari; Erna Zumrotun; Nina Sofiana (Universitas Muhammadiyah Sorong, 2023)
This research aims to analyze the implementation of the project to strengthen the profile of Pancasila students in forming the character of students as well as the supporting and inhibiting factors in its implementation. The type of research used is qualitative research. The subjects of this research were students, class IV teachers and principals of SDN 1 Bandung Mayong Jepara. The data collection methods used were observation, interviews and documentation. The results of this research indicate that the implementation of the project to strengthen the profile of Pancasila students at SDN 1 Bandung Mayong has been carried out well. Of the six themes, in the 2022/2023 academic year, even semester, SDN 1 Bandung has implemented one theme, namely